2002
DOI: 10.1152/ajpendo.00557.2001
|View full text |Cite
|
Sign up to set email alerts
|

Lactate induces insulin resistance in skeletal muscle by suppressing glycolysis and impairing insulin signaling

Abstract: tion of plasma lactate levels induces peripheral insulin resistance, but the underlying mechanisms are unclear. We examined whether lactate infusion in rats suppresses glycolysis preceding insulin resistance and whether lactate-induced insulin resistance is accompanied by altered insulin signaling and/or insulin-stimulated glucose transport in skeletal muscle. Hyperinsulinemic euglycemic clamps were conducted for 6 h in conscious, overnight-fasted rats with or without lactate infusion (120 mol ⅐ kg Ϫ1 ⅐ min Ϫ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 37 publications
8
88
1
1
Order By: Relevance
“…The role of lactate as a glucose-competing agent is supported by recent clamp studies showing that increased lactate utilisation was associated with decreased glucose disappearance during moderate intensity exercise [30]. Similarly, animal studies observed reduced glucose uptake by the muscle in the presence of hyperlactataemia [31][32][33]. Due to the design of the present study we can only speculate on potential mechanisms related to elevated lactate levels during IHE.…”
Section: Discussionsupporting
confidence: 54%
“…The role of lactate as a glucose-competing agent is supported by recent clamp studies showing that increased lactate utilisation was associated with decreased glucose disappearance during moderate intensity exercise [30]. Similarly, animal studies observed reduced glucose uptake by the muscle in the presence of hyperlactataemia [31][32][33]. Due to the design of the present study we can only speculate on potential mechanisms related to elevated lactate levels during IHE.…”
Section: Discussionsupporting
confidence: 54%
“…Glucose homeostasis in glucokinase-expressing transgenic mice It has been suggested that high levels of circulating lactate observed during obesity may contribute to insulin resistance [32][33][34][35][36][37]. However, no difference in serum insulin concentration was observed in fed or starved transgenic mice compared with controls (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that high levels of circulating lactate observed during obesity contribute to insulin resistance by decreasing glucose utilisation by skeletal muscle and enhancing hepatic gluconeogenesis [32][33][34][35][36][37]. Plasma lactate is elevated in obese individuals and this increase is higher when obesity is associated with type 2 diabetes [32].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia during and after HIE in type 1 diabetes was likely due to a lack of physiological hyperinsulinemia (10). Interestingly, based on findings in rodent muscle (18), the high plasma lactate in both groups may have induced acute insulin resistance. This may have further contributed to the hyperglycemia in type 1 diabetes and likely explains the lack of fall in plasma glucose during recovery in control subjects, despite high insulin.…”
Section: -Effects Of Intermittent Maximal Exercise (Hatched Bars) Befmentioning
confidence: 95%